Pulmonary alveolar proteinosis complicated by lung cancer with favorable prognosis: a case report and literature review - Wu, Ying; Guan, Wenhui; Deng, Jiaxi; Mo, Wenwei; Xu, Beini; Zhang, Jiahao; Jiang, Huixin; Liu, Jie (Frontiers in Oncology, 2024)
With the increasing incidence of lung cancer, the coexistence of pulmonary alveolar proteinosis (PAP) and lung cancer is becoming more common. However, the standard treatment protocols for patients with both conditions are still being explored. The conflict between the rapidly evolving therapeutic approaches for tumors and the limited treatment options for PAP presents a significant challenge for clinicians. Determining the optimal timing of treatment for both conditions to maximize patient benefit is a clinical conundrum. Here, we report a rare case of PAP complicated by lung adenocarcinoma, where interstitial lung changes worsened after neoadjuvant therapy but improved significantly following surgical resection of the lung adenocarcinoma. This case highlights the importance of prioritizing tumor treatment in patients with lung cancer complicated by PAP and examines the interplay between the two conditions, as well as potential therapeutic strategies.